The Effect of Using Clustering Strategy by Random Card Media on The Students' English Vocabulary - Rita Harisma; Irma Isroyani Siregar; Vivin Agustin (International Journal of Science and Applied Science: Conference Series, 2022)
This research was carried out to investigate the effect of using a clustering strategy by random card media on the students’ English Vocabulary. The population of this research was the seventh-year students of SMP Muhammadiyah 05 Medan 2019-2020 which consisted of 64 students. By using total sampling, the total sample of this research was 64 students. The sample of this research was all of the population. The sample was divided into two groups, class VII -1 was for an experimental group that used Clustering Strategy and class VII-2 was for a control group that using Lecturing strategy. This research was using an experimental research method. The test was taken from the students’ worksheets. The test was given to the experimental and control groups in a multiple-choice test consisting of 20 items to know the significant effect of using the clustering strategy and lecturing strategy. The finding of the research showed that there was a significant effect of using the clustering strategy by random card media on the students' English vocabulary because tobserve was higher than ttable (3,16 > 1,670). It meant that the alternative hypothesis (Ha) was accepted.